Change and continuity in agrarian relations - Karanth, G. K. (Gopal Krishna), 1952- (New Delhi : Concept Pub. Co., 1995)
Case study of Rajapura, village in Bangalore District.
Includes bibliographical references (p. [160]-167) and index.
Keywords: Land reform -- India -- Bangalore; Food crops -- India -- Bangalore; Agriculture -- Social aspects -- India -- Bangalore; Social structure -- India -- Kanartaka -- History